PENGELOLAAN PEMUNGUTAN PAJAK RESTORAN DI KABUPATEN TANAH DATAR TAHUN 2016-2018 - Suci Angraini; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Restaurant tax is one of the biggest local original government revenue in Tanah Datar district. The potential of restaurant tax revenue in Tanah Datar Regency exceedsmore than 1 billion, but it is still not optimal yet. There are still several restaurants that do not pay the tax. In addition, there are still arrears in tax payments. Then, many restaurants are not recorded in the Local Government Finance Office of Tanah Datar. Those problems indicate that Tanah Datar District government regulation is still not up to date in terms of managing restaurant tax collection.Management restaurant tax collection in Tanah Datar Districk can be seen from: Planning, Organizing, Acting, Controlling. Based on the results of the analysis, it can be concluded that in management of restaurant tax collection in Tanah Datar District government regulations are still weak in terms of restaurant tax collection, lack of human resources quality to manage restaurant taxes, and the lack of public awareness of the importance of taxes for development. Based on the several weaknesses above, Local Government Finance Office of Tanah Datar is suggesed to be able to resolve wisely to increase restaurant tax revenue so that it runs well. Keyword: Restaurant Tax, Management, Local Government Finance Office